1985
DOI: 10.1021/ja00295a026
|View full text |Cite
|
Sign up to set email alerts
|

Ring transformation equilibrium (bond switch) in 5-(2-aminovinyl)isothiazole system via hypervalent sulfurane. Synthesis, structure determination, and kinetic study

Abstract: Reaction of 3-aryl-5-methylisothiazoles (4) with aromatic nitriles afforded the adducts 3, 5-(2-amino-2-arylvinyl)-3-arylisothiazole derivatives, in the presence of LDA. By employing p-chlorobenzonitrile-15lV, the presence of ring transformation from one isothiazole (a form) to another isothiazole {ß form) was verified. By spectral analyses of 3 compared with 5-[2-(silylamino)-2-arylvinyl]-3-arylisothiazole (13-Z), 3 was concluded to have trans geometry (3-Z) with respect to two aromatic rings to arrange N-8••… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…The solvent effect by benzene and DMSO leads minor change for the barriers. The substitutions at Y (4) and Y (6) do not change the energy diagrams in any significance except for the reactant and product structures. Therefore, it is concluded that the unimolecular bond-switching reactions cannot proceed thermally.…”
Section: ¹1mentioning
confidence: 93%
See 4 more Smart Citations
“…The solvent effect by benzene and DMSO leads minor change for the barriers. The substitutions at Y (4) and Y (6) do not change the energy diagrams in any significance except for the reactant and product structures. Therefore, it is concluded that the unimolecular bond-switching reactions cannot proceed thermally.…”
Section: ¹1mentioning
confidence: 93%
“…Therefore, the hypervalent NSN bond energy itself could not been evaluated experimentally. On the other hand, such phenomenon cannot be found for the corresponding oxygen analogs, i.e., 1,2,4-oxadiazole and isoxazole systems (6) in Scheme 4. 6 The difference between 2 and 6 is only the center atom.…”
mentioning
confidence: 89%
See 3 more Smart Citations